Thermal and Aerodynamic Researches of Staggered Bundles for Choice of an Effective Spacing of Round-Finned Tubes - V. B. Kuntysh; A. B. Sukhotskii; G. S. Marshalova; V. V. Dudarev; V. N. Farafontov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2019)
The results of an experimental study of local modeling of convective heat transfer and aerodynamic resistance of staggered six-row bundles of bimetallic tubes with spiral knurled aluminum fins under transverse air flow in the range of its velocity alteration in a compressed bundle section of 1.9−11.0 m/s are presented. The velocity range covers the possible modes of operation of industrial air coolers (AVO). The fins with a diameter of approximately 57 mm are rolled on a steel supporting tube with an outer diameter of 25 mm. Tube finning ratio j = 19.26. Such tubes are widely used in the heat exchange sections of AVO of natural gas, in particular, at “Gribanovskii Engineering Plant” JSC (Russia). To measure the reduced heat transfer coefficients, an electric calorimeter had been developed by the authors with a power input of 600−1300 W. The temperature of the wall surface at the base of the fins did not exceed the range of 77–92 °C. The transverse tube spacing in bundles S1was 64.0 or 68.0 mm, while the longitudinal spacing S2 was 54.4 or 50.0 mm. The heat transfer of each transverse row of six-row bundles was measured, as well as the average heat transfer and aerodynamic drag, which are summarized by the similarity equation of a power type. The heat transfer rate of the last transverse row in the direction of air movement is 0–5 % lower than the heat transfer rate of the stabilized rows, and here new features of heat transfer variations in the insufficiently studied area of spacing changes S1 and S2 have been found. The thermal contact resistance (TCR) was measured in the range of the average temperature of the contact surfaces tк = (79–95) оС, and no dependence of the value of TCR on tк for the specified interval was found. The numerical average value of TCR was Rк = 2,13 × 10–4 m2×K/W, which is typical for reliable mechanical connection of the finned aluminum shell with the supporting steel tube made of carbon steel. The results of variant thermal and aerodynamic calculations with the use of the obtained data established the technical and economic feasibility of placing tubes at the vertices of an isosceles triangle with spacing S1 = 68–69 mm and S2 = 55 mm with failure to use the location of the tubes along an equilateral triangle with S1 = S2' = 64 mm (where S2' – is diagonal spacing). With Q = idem and other conditions being equal, the number of tubes on AVO decreases by 5.7 % with a decrease in power consumption to 4.0 %.